Ascribing Meaning to Occupation: An Example From Healthy, Working Mothers. (July 2016) - Avrech Bar, Michal; Forwell, Susan; Backman, Catherine L.
Ascribing meaning to occupation is a multifaceted process. Understanding this process is illusive, yet fundamental to theory and practice. The objective is to describe the meaning that mothers ascribe to their occupations. A secondary analysis was conducted with data from a convenience sample of 35 Israeli mothers, ages 25 to 45 years. Data were collected using the Occupational Performance History Interview as part of a larger study. Interviews were transcribed verbatim and content analysis applied. Two main categories emerged: the meaning of "giving" (investing values) and the meaning of "receiving" (ensuring needs are met). Values such as responsibility require mothers to do occupations they find less desirable than others associated with the mothering role. The study illustrates how values and needs are intertwined to contribute to the meaning of occupation. Moreover, meaningful occupations can be undesirable but doing them arises from the values that drive mothers to fulfill this role.